An artful contribution to our planetary concerns. Issue 1 (14th October 2020) - Losch, Andreas
Abstract: Adam Pryor's fresh understanding of the imago Dei as a refraction of the Divine is much needed in an age of science and climate change. Well informed by astrobiological insights, his approach presents what I would call a deep reconceptualization of the imago Dei as a planetary phenomenon. The human planetary phenomenon, however, currently faces its own limitations. This is an ethical reality, which is touched upon by Pryor, but could have been expressed more clearly and deliberately. The review attempts to develop some of Pryor's thoughts in dialoue with Hans Jonas, and with my own thoughts on "planetary sustainability."